2008
DOI: 10.1128/mcb.00040-08
|View full text |Cite
|
Sign up to set email alerts
|

Musashi1 Modulates Mammary Progenitor Cell Expansion through Proliferin-Mediated Activation of the Wnt and Notch Pathways

Abstract: The RNA-binding protein Musashi1 (Msi1) is a positive regulator of Notch-mediated transcription in Drosophila melanogaster and neural progenitor cells and has been identified as a putative human breast stem cell marker. Here we describe a novel functional role for Msi1: its ability to drive progenitor cell expansion along the luminal and myoepithelial lineages. Expression of Msi1 in mammary epithelial cells increases the abundance of CD24 hi Sca-1 ؉ , CD24 hi CD29 ؉ , CK19, CK6, and double-positive CK14/CK18 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
141
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(159 citation statements)
references
References 74 publications
(65 reference statements)
10
141
1
Order By: Relevance
“…Consistent with its role in self-renewal, Msi1 expression is positively correlated with a labelretaining and side population human breast epithelial cells enriched in ERα, p21 Cip1 , CK19 and double-positive CK14/CK18 progenitor cells (Smalley and Clarke, 2005;Clarke et al, 2005). When Msi1 is overexpressed in murine mammary epithelial cells, CD24 hi /Sca-1 + , CD24 hi /CD29 + , CK14 + /CK18 + and CK6 + and CK19 + expression is enhanced in mammary stem and progenitor cells Wang et al, 2008). Msi1 acts in a unique autocrine pathway which consists of increased secretion of the growth factor Proliferin, loss of the Wnt inhibitor DKK3, activation of Wnt and Notch signaling Wang et al, 2008).…”
Section: Function Of Musashi1 In Normal and Cancer Stem Cellsmentioning
confidence: 64%
See 2 more Smart Citations
“…Consistent with its role in self-renewal, Msi1 expression is positively correlated with a labelretaining and side population human breast epithelial cells enriched in ERα, p21 Cip1 , CK19 and double-positive CK14/CK18 progenitor cells (Smalley and Clarke, 2005;Clarke et al, 2005). When Msi1 is overexpressed in murine mammary epithelial cells, CD24 hi /Sca-1 + , CD24 hi /CD29 + , CK14 + /CK18 + and CK6 + and CK19 + expression is enhanced in mammary stem and progenitor cells Wang et al, 2008). Msi1 acts in a unique autocrine pathway which consists of increased secretion of the growth factor Proliferin, loss of the Wnt inhibitor DKK3, activation of Wnt and Notch signaling Wang et al, 2008).…”
Section: Function Of Musashi1 In Normal and Cancer Stem Cellsmentioning
confidence: 64%
“…Although Msi1 and Msi2 have differing patterns of expression and roles within the cell (Aubert et al, 2003;Chan et al, 2006;Siddall et al, 2006;Sugiyama-Nakagiri et al, 2006;Sgubin et al, 2007;Kharas et al, 2010), both Msi1 and Msi2 are required for brain stem cell self-renewal (Sakakibara et al, 2002). In mammalian cells, Msi1 denotes multipotent stem cells in the brain (Sakakibara et al, 1996;Keyoung et al, 2001;McGuckin et al, 2004;Uchida et al, 2004), intestine (Kayahara et al, 2003;Nishimura et al, 2003;Sakatani et al, 2005) , breast (Clarke, 2005;Wang et al, 2008), and hair follicles (Sugiyama-Nakagiri et al, 2006).…”
Section: The Musashi1 Rna-binding Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as well as other stem/progenitor cells, putative human breast stem cells were discovered in the mammary gland using specific antibodies for Msi1 and p21 WAF1 (23). Wang et al found that much more committed progenitor cells in the mammary gland also express Msi1 protein, although luminal and myoepithelial progenitor cells do not express it (47). Likewise, SugiyamaNakagiri et al reported that Msi1 and Msi2 are expressed in the epidermis and hair follicles of mice from E14.5 until adulthood (24).…”
Section: Somatic Stem Cells and Msi1 Protein Functionmentioning
confidence: 99%
“…Although Wang et al (2008) proposed that the Msi1 protein is involved in both Notch and Wnt signaling pathways as a novel autocrine process (Nagata et al, 2006;Glazer et al, 2008), details of the mechanism remain unclear, and direct regulators of Msi1 have not been identified.…”
Section: Novel Finding For the Functions Of Musashi Proteinsmentioning
confidence: 99%